The metabolism of the synthetic cannabinoids ADB‐BUTINACA and ADB‐4en‐PINACA and their detection in forensic toxicology casework and infused papers seized in prisons. Issue 4 (10th December 2021) - Kronstrand, Robert; Norman, Caitlyn; Vikingsson, Svante; Biemans, Anoek; Valencia Crespo, Bryan; Edwards, Darren; Fletcher, Daniel; Gilbert, Nicolas; Persson, Mattias; Reid, Robert; Semenova, Olga; Al Teneiji, Faisal; et al.
Abstract: Early warning systems detect new psychoactive substances (NPS), while dedicated monitoring programs and routine drug and toxicology testing identify fluctuations in prevalence. We report the increasing prevalence of the synthetic cannabinoid receptor agonist (SCRA) ADB‐BUTINACA ( N ‐[1‐amino‐3, 3‐dimethyl‐1‐oxobutan‐2‐yl]‐1‐butyl‐1 H ‐indazole‐3‐carbox‐amide). ADB‐BUTINACA was first detected in a seizure in Sweden in 2019, and we report its detection in 13 routine Swedish forensic toxicology cases soon after. In January 2021, ADB‐BUTINACA was detected in SCRA‐infused papers seized in Scottish prisons and has rapidly increased in prevalence, being detected in 60.4% of the SCRA‐infused papers tested between January and July 2021. In this work, ADB‐BUTINACA was incubated with human hepatocytes (HHeps), and 21 metabolites were identified in vitro, 14 being detected in authentic case samples. The parent drug and metabolites B9 (mono‐hydroxylation on the n ‐butyl tail) and B16 (mono‐hydroxylation on the indazole ring) are recommended biomarkers in blood, while metabolites B4 (dihydrodiol formation on the indazole core), B9, and B16 are suitable biomarkers in urine. ADB‐4en‐PINACA ( N ‐[1‐amino‐3, 3‐dimethyl‐1‐oxobutan‐2‐yl]‐1‐[pent‐4‐en‐1‐yl]‐1 H ‐indazole‐3‐carboxamide) was detected in Scottish prisons in December 2020, but, unlike ADB‐BUTINACA, prevalence has remained low. ADB‐4en‐PINACA was incubated with HHeps, and 11 metabolites were identified. Metabolites E3 (dihydrodiol formed in the tail moiety) and E7 (hydroxylation on the linked/head group) are the most abundant metabolites in vitro and are suggested as urinary biomarkers. The in vitro potencies of ADB‐BUTINACA (EC50, 11.5 nM and ADB‐4en‐PINACA (EC50, 11.6 nM) are similar to that of MDMB‐4en‐PINACA (EC50, 4.3 nM). A third tert ‐leucinamide SCRA, ADB‐HEXINACA was also detected in prison samples and warrants further investigation. Abstract : The detection, metabolism, and pharmacology of ADB‐BUTINACA and ADB‐4en‐PINACA are described following their detection in infused papers seized in prisons and in forensic toxicology casework.